2020
DOI: 10.1002/alr.22578
|View full text |Cite
|
Sign up to set email alerts
|

A primer on viral‐associated olfactory loss in the era of COVID‐19

Abstract: Early reports have suggested that smell loss may be an early symptom associated with the pandemic known as COVID-19. The possibility that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) might cause olfactory dysfunction is certainly plausible. Patients presenting to specialized smell clinics are commonly diagnosed with upper This article is protected by copyright. All rights reserved. respiratory infection (URI)-associated olfactory loss and most are presumed to be viral related. In acute phases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
171
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(187 citation statements)
references
References 35 publications
3
171
0
7
Order By: Relevance
“…49,50 Last, the fact that other sinonasal symptoms appear to be less common argues against the possibility that COVID-19-mediated olfactory loss is related to nasal inflammation, mucosal edema, and airflow limitation, as is the case with other upper respiratory infections. 39 There are several important limitations to this review. First, given the controversial relationship between olfactory and gustatory dysfunction and COVID-19, these symptoms may be underreported in many of the studies included.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…49,50 Last, the fact that other sinonasal symptoms appear to be less common argues against the possibility that COVID-19-mediated olfactory loss is related to nasal inflammation, mucosal edema, and airflow limitation, as is the case with other upper respiratory infections. 39 There are several important limitations to this review. First, given the controversial relationship between olfactory and gustatory dysfunction and COVID-19, these symptoms may be underreported in many of the studies included.…”
Section: Discussionmentioning
confidence: 98%
“…Although olfactory loss commonly presents in the setting of upper respiratory infections, the pathogenesis responsible for COVID-19-mediated olfactory or gustatory disturbances has not yet been definitively identified. 39 One potential mechanism is that COVID-19 may specifically target cells in the sinonasal tract, including the olfactory epithelium. 33,40 The virus appears to target the angiotensin-converting enzyme 2 (ACE2) receptor, 41 perhaps the highest levels of which are expressed in goblet and ciliated cells in the nasal epithelium, 42 as well as in the lung and by respiratory tract epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The most common symptoms of the disease are fever, cough, headache, myalgia, dyspnea and diarrhea [3]. Smell and taste disorder started to draw attention as the symptom that started as the earliest and ended as the latest [4]. The disease starts as a simple respiratory infection and causes pneumonia in a short time.…”
Section: Introductionmentioning
confidence: 99%
“…It is not yet known whether smell loss is long-term in COVID-19. However, in some patients, it has been reported to continue even after the disease has passed [4,10]. Although there are many new studies on COVID-19 related to loss of smell, no study has yet been conducted on the radiological ndings in the paranasal sinuses [4,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The present study revealed that 95.5% patients with loss of taste and 82.1% patients with loss of smell recovered spontaneously, and most of them in 2-week time, although the severe impairment of olfactory and smell function may lead to delayed recovery. The spontaneous recovery may be a result of regeneration of the damaged olfactory epithelium and taste buds (29). Previously, oral and topical corticosteroids have been proposed to treat viral-associated olfactory loss.…”
Section: Discussionmentioning
confidence: 99%